Stabilization of milk-sphingomyelin gel phases by glycosphingolipids: An in-vitro study on the characteristics of milk sphingolipid gel phases - Sazzad, Md Abdullah Al; Lönnfors, Max; Yang, Baoru (Chemistry and physics of lipids, 2025)
Sphingolipids constitute a class of bioactive lipids essential for the structural and functional integrity of milk fat globule membrane (MFGM). Milk sphingomyelin (milk-SM), as a key component of MFGM, contributes to the stability of milk fat emulsions. Milk-SM and other sphingolipids, like glycosphingolipids (GSL), coexist in the same outer bilayer of MFGM, suggesting significant role of their interaction in shaping the structural properties and functions of MFGM. In this study, using an in-vitro model membrane system, we investigated the impact of various GSLs, including cerebrosides and gangliosides, on the lateral segregation and phase behavior of milk-SM in 1-palmitoyl-2-oleoyl-sn-glycero-3-phosphocholine bilayers. We also incorporated N-palmitoyl-D-erythro-ceramide for a comparative analysis of the impacts of sphingolipid head groups. The lateral segregation of sphingolipid gel phases was assessed using trans-parinaric acid (tPA) fluorescence lifetime analysis, and their thermostability was examined using steady-state fluorescence anisotropy of tPA. Additionally, we assessed the binary interactions between milk-SM and GSLs using the steady-state fluorescence anisotropy of 1,6-diphenyl-1,3,5-hexatriene (DPH). The results indicate that GSLs promote the lateral segregation and stabilization of milk-SM-rich gel phases in the membrane bilayers. The size of the GSL head groups significantly influenced the degree of this stabilization, with larger head groups demonstrating diminished interactions with milk-SM. Our results provide valuable insights into the role of various sphingolipid structures in membrane phase behavior and organization. Comprehensive understanding of the interactions of these important sphingolipids in MFGM environment is crucial due to their structural and functional importance in dairy and nutritional applications. •GSLs significantly promoted the milk-SM gel phases in a model membrane bilayer.•Lipid phase separation was detected by fluorescence lifetime analysis of tPA.•Steady-state anisotropy of tPA and DPH was used to detect the phase thermostability.•The size of SL head group had a major impact on membrane properties.•Increased head group size leads to restricted interaction with neighboring lipids.